Traditional knowledge and environmental conservation among indigenous people in Ranau, Sabah - Ab. Halim, Adlina; Jawan, Jayum; Ismail, Sri Rahayu; Othman, Normala; Masnin, Mohd Hadzrul (Global Journals Inc., 2013)
Traditional knowledge is a form of continuation of the inherited knowledge of a race from its forefathers. This traditional knowledge represents a holistic understanding of an indigenous society towards its day-to-day practices and environment, based on their life experiences, interacting with nature over a span of countless centuries. The bulk of this traditional knowle-dge has been adapted by means of traditional songs, stories, legends, dreams, and also other methods and living practices of the indigenous societies. At times, it is translated in the form of customs that are inherited from father to son or from mother to daughter. This knowledge is disseminated first-hand from one individual to another. Indigenous societies are citizens in free countries who are considered as natives, who have their ancestry from inhabitants who had been residing in a certain country or geographical region of an indepen-dent country, at the time of colonial conquest.